The role of MARCH9 in colorectal cancer progression - Liu, Hua; Chen, Biao; Liu, Lian-Lin; Cong, Lin; Cheng, Yong (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the third most common cancer with a high global incidence and mortality. Mutated genes or dysregulated pathways responsible for CRC progression have been identified and employed as biomarkers for diagnosis and prognosis. In this study, a ubiquitination regulator, MARCH9, was shown to accelerate CRC progression both in vitro and in vivo. CRC samples from The Cancer Genome Atlas (TCGA) showed significantly upregulated MARCH9 expression by individual cancer stage, histological subtype, and nodal metastasis status. Knockdown of MARCH9 inhibited, while MARCH9 overexpression promoted, CRC cell proliferation and migration. Knockdown of MARCH9 also induced CRC cell apoptosis and caused cell cycle arrest. Further investigation showed that MARCH9 promoted CRC progression by downregulating the expression of a deubiquitinase cylindromatosis (CYLD) gene and activating p65, a member of the nuclear factor-κB (NF-κB) protein family. Finally, in vivo xenograft studies confirmed that MARCH9 knockdown suppressed tumor growth in nude mice. Thus, this study demonstrated that MARCH9 may be a novel and effective therapeutic target for CRC therapy.